Lithium metal battery and its preparation method and application
By introducing phase change materials with core-shell structures into the gel electrolyte of lithium batteries and forming chemical bonds with the three-dimensional crosslinking network, the problems of uneven distribution and unfixed position of phase change materials are solved, and the inhibition of thermal runaway in lithium batteries and the improvement of battery performance is achieved.
Patent Information
- Application Number
- CN202210920467.2
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2022-08-02
- Publication Date
- 2025-03-25
- Estimated Expiration
- 2042-08-02
AI Technical Summary
The thermal runaway caused by the internal short circuit of lithium batteries, especially the uneven distribution of phase change materials in solid electrolytes and the position is not fixed, resulting in the impact of ion conduction performance and degradation of cycling performance and safety performance.
A phase change material with a core-shell structure is introduced into the gel electrolyte, and a chemical bond is formed with a three-dimensional cross-linking network through the shell to achieve positional fixation of the phase change material and avoid settlement and flow problems.
Effectively suppress the thermal runaway of lithium batteries, improve ion conduction performance, and improve the cycling and safety performance of the battery.
Smart Images

Figure CN115172859B_ABST
Abstract
Description
Technical Field
[0001] The present application relates to the technical field of lithium batteries, and in particular to a lithium metal battery and a preparation method and application thereof. Background Art
[0002] Lithium batteries have the advantages of long life, high energy density and high operating voltage, and are one of the most promising energy storage technologies. At present, lithium batteries have been widely used in consumer electronics and electric vehicles. The large-scale application of lithium batteries has put forward higher requirements for their safety performance. Thermal runaway is a key factor affecting the safety performance of lithium batteries. The main factors of thermal runaway of lithium batteries can be divided into external short circuit, external high temperature and internal short circuit. Standardizing the use conditions and use environment of lithium batteries can effectively avoid thermal runaway of batteries caused by external factors (such as external short circuit, external high temperature), but for internal short circuits caused by battery abuse, it will induce the internal temperature to continue to rise, resulting in the shrinkage and melting of the diaphragm, and severe thermal runaway in the later stage is difficult to remedy.
[0003] Introducing phase change materials into the electrolyte is one of the effective strategies to solve the thermal runaway problem in lithium batteries. The prior art proposes to compound the composite phase change material with polyethylene oxide and polynorbornene by kneading, and then make a cast sheet through a screw extrusion process, and then make a composite phase change solid electrolyte membrane through processes such as stretching, mirror roller shaping, cooling and winding. However, the random blending of the phase change material and the solid electrolyte substrate is likely to cause local accumulation of the phase change material in the diaphragm, affecting the ionic conductivity of the solid electrolyte and the energy storage performance of the phase change material. In addition, the phase change material that is not fixed in the solid electrolyte is likely to flow due to the phase change, thereby generating local voids and affecting the cycle performance of the battery. Summary of the invention
[0004] The embodiments of the present application provide a lithium metal battery and a preparation method and application thereof, which can achieve uniform dispersion and position fixation of a phase change material in a gel solid electrolyte, so as to improve the inhibitory effect of the phase change material on thermal runaway of the lithium battery, avoid the influence of the phase change material on the internal ion conductivity of the solid electrolyte due to phase change flow, and thereby improve the electrical performance, cycle performance and safety performance of the lithium metal battery.
[0005] In a first aspect, an embodiment of the present application provides a lithium metal battery, including a gel electrolyte;
[0006] The gel electrolyte comprises a phase change material and a three-dimensional cross-linked network, the phase change material comprises an inner core and a shell layer on the surface of the inner core, and the inner core comprises a phase change substance;
[0007] The phase change material is bonded to the three-dimensional cross-linked network.
[0008] Optionally, the shell layer comprises a polymer and silicon dioxide, and a monomer of the polymer comprises a silane coupling agent containing a carbon-carbon double bond.
[0009] Optionally, the mass ratio of the polymer to the silica is 1:1 to 1:1000.
[0010] Optionally, the mass ratio of the polymer to the silica is 1:1 to 1:100.
[0011] Optionally, the silane coupling agent contains an oxygen-containing group, and the oxygen-containing group includes any one of an alkoxy group, a siloxy group or a group shown in formula a;
[0012]
[0013] Optionally, the silane coupling agent is selected from any one of the substances shown in Formula I;
[0014]
[0015] R1 is selected from any one of C1-C5 siloxy, C1-C5 alkoxy or the group represented by formula a;
[0016] R2 is selected from any one of the groups shown in formula b or the groups shown in formula c;
[0017]
[0018]
[0019] R3 and R5 are independently selected from any one of C1-C3 alkylene, R4 is selected from any one of H and C1-C3 alkyl, and n is 0 or 1.
[0020] Optionally, the silane coupling agent includes one or more of methacryloxypropyltrimethoxysilane, vinyltri(2-methoxyethoxy)silane, allyltrimethoxysilane, allyltri(trimethylsiloxy)silane, and (2-methylallyl)trimethylsilane.
[0021] Optionally, the phase change temperature of the phase change material is 30 to 85°C;
[0022] Preferably, the phase change temperature of the phase change material is 65°C to 75°C.
[0023] Optionally, the phase change material includes C 20 ~C 50 Higher aliphatic hydrocarbons, C 10 ~C 50 Higher fatty acids, C 20 ~C 50 Higher fatty acid esters or C 20 ~C50 At least one of higher fatty alcohols.
[0024] Optionally, the average particle size of the phase change material is 0.1 μm to 1 μm.
[0025] Optionally, the shell layer has a thickness of 1 nm to 10 nm.
[0026] Optionally, the three-dimensional cross-linked network is obtained by polymerization of monomers;
[0027] The monomer includes at least one of polyoxyethylene and its derivatives, polyvinylidene fluoride and its derivatives, or polycarbonate and its derivatives;
[0028] Preferably, the polyoxyethylene derivative comprises at least one of branched polyoxyethylene, polyoxyethylene / polycarbonate block copolymer, and polyoxyethylene / polysulfone block copolymer;
[0029] The polyvinylidene fluoride derivative includes at least one of a vinylidene fluoride / trifluoroethylene copolymer and a vinylidene fluoride / hexafluoropropylene copolymer;
[0030] The polycarbonate derivative includes at least one of branched polycarbonate and polycarbonate / polyethylene oxide copolymer.
[0031] Optionally, the mass percentage of the phase change material in the phase change gel electrolyte is 1% to 10%;
[0032] Preferably, the mass percentage of the phase change material in the gel electrolyte is 4% to 6%.
[0033] In a second aspect, the present application provides a method for preparing the lithium metal battery, wherein the method for preparing the gel electrolyte comprises the following steps:
[0034] (1) adding a silane coupling agent to a material containing a phase change material and silicon dioxide to obtain an emulsion;
[0035] (2) adding an initiator to the emulsion obtained in (1) under an inert atmosphere, and stirring at 60° C. to 80° C. to obtain a phase change material having a core-shell structure;
[0036] (3) The phase change material obtained in (2), the electrolyte, the polymerizable monomer, the crosslinking agent and the initiator are uniformly mixed and reacted at 65° C. to 75° C. to obtain a gel electrolyte.
[0037] In a third aspect, an embodiment of the present application provides an electrical device, wherein the electrical device comprises any one of the above-mentioned lithium metal batteries.
[0038] The beneficial effects brought about by the technical solutions provided by some embodiments of the present application include at least:
[0039] The present application introduces a phase change material into a gel electrolyte. On the one hand, the phase change material absorbs the heat energy generated during the cycle of the lithium metal battery during the phase change process, so as to avoid heat accumulation and thermal runaway inside the lithium metal battery. On the other hand, since the phase change material is a phase change material with a core-shell structure, a shell layer is formed on the surface of the phase change material to cover the phase change material, and the shell layer is chemically bonded to the three-dimensional cross-linked network to form covalent cross-links with the phase change material to fix the phase change material on the three-dimensional cross-linked network. This can effectively solve the problem of uneven distribution of the phase change material in the gel electrolyte due to sedimentation and easy flow during the phase change process, thereby improving the cycle performance and safety performance of the lithium metal battery. BRIEF DESCRIPTION OF THE DRAWINGS
[0040] In order to more clearly illustrate the embodiments of the present application or the technical solutions in the prior art, the drawings required for use in the embodiments or the description of the prior art will be briefly introduced below. Obviously, the drawings described below are only some embodiments of the present application. For those skilled in the art, other drawings can be obtained based on these drawings without paying any creative work.
[0041] Figure 1 This is a schematic diagram of the structure of the phase change material in the embodiment of the present application;
[0042] Figure 2 Schematic diagram of the structure of the gel electrolyte in the embodiment of the present application. DETAILED DESCRIPTION
[0043] In order to make the purpose, technical solution and advantages of the present application more clearly understood, the present application is further described in detail below in conjunction with the accompanying drawings and embodiments. It should be understood that the specific embodiments described herein are only used to explain the present application and are not used to limit the present application.
[0044] For simplicity, this application only explicitly discloses some numerical ranges. However, any lower limit can be combined with any upper limit to form an unclearly recorded range; and any lower limit can be combined with other lower limits to form an unclearly recorded range, and any upper limit can be combined with any other upper limit to form an unclearly recorded range. In addition, although not clearly recorded, each point or single value between the range endpoints is included in the range. Thus, each point or single value can be combined with any other point or single value as its own lower limit or upper limit or with other lower limits or upper limits to form an unclearly recorded range.
[0045] In the detailed description and claims, a list of items connected by the terms "at least one of," "at least one of," "at least one of," or other similar terms may mean any combination of the listed items. For example, if items A and B are listed, the phrase "at least one of A and B" means only A; only B; or A and B. In another example, if items A, B, and C are listed, the phrase "at least one of A, B, and C" means only A; or only B; only C; A and B (excluding C); A and C (excluding B); B and C (excluding A); or all of A, B, and C.
[0046] Adding phase change materials to solid electrolytes can improve thermal runaway inside lithium batteries, and the distribution relationship of phase change materials in solid electrolytes will affect the improvement effect of thermal runaway inside lithium batteries. If the phase change materials are unevenly distributed in the solid electrolyte, such as local accumulation of phase change materials in the solid electrolyte, the locally accumulated phase change materials cannot uniformly absorb and disperse the heat energy generated by the lithium metal battery during the charge-discharge cycle, which will lead to a decrease in the inhibitory effect of the phase change materials on thermal runaway of lithium batteries.
[0047] In addition, if the position of the phase change material in the solid electrolyte cannot be fixed, the phase change material will flow due to its own phase change, thereby creating gaps, affecting the ion conduction performance inside the solid electrolyte and reducing the electrical performance, cycle performance and safety performance of the lithium metal battery.
[0048] The prior art uses phase change materials and solid electrolyte substrates to prepare solid electrolyte membranes by kneading and compounding. However, the random blending method easily causes local accumulation of phase change materials in the diaphragm. At the same time, since the phase change material is not fixed on the solid electrolyte, the phase change material will flow due to phase change, affecting the cycle performance of the battery.
[0049] In order to solve the above technical problems, the first aspect of the present application proposes a lithium metal battery, which includes a gel electrolyte; the gel electrolyte includes a phase change material and a three-dimensional cross-linked network, the phase change material includes a core and a shell on the surface of the core, and the core includes a phase change substance; the phase change material is bonded to the three-dimensional cross-linked network.
[0050] Furthermore, the gel electrolyte includes a phase change material, a three-dimensional cross-linked network and an electrolyte, the phase change material includes a core and a shell, the core and the shell are a core-shell structure, and the shell of the phase change material is chemically bonded to the three-dimensional cross-linked network through a carbon-carbon double bond.
[0051] The present application achieves a fixed position of the phase change material on the three-dimensional cross-linked network by coating the phase change material with a polymer, i.e., forming a shell layer on the surface of the phase change material to wrap the phase change material, and utilizing the shell layer and the three-dimensional cross-linked network to covalently cross-link the phase change material with the three-dimensional cross-linked network by chemical bonding. This can effectively solve the problem of easy flow of the phase change material in the solid electrolyte, and is beneficial to improving the cycle performance and safety performance of the lithium metal battery.
[0052] In some exemplary embodiments, the shell layer includes a polymer and silicon dioxide, and a monomer of the polymer includes a silane coupling agent containing a carbon-carbon double bond.
[0053] Furthermore, the silicon dioxide is nano silicon dioxide, and the silane coupling agent is bonded to the surface of the nano silicon dioxide.
[0054] Combination Figure 1 As shown, Figure 1 The light-colored part in the inner shell is a phase change material, the dark-colored lamellae are shell layers, and the protrusions (particles) on the dark-colored lamellae are nano-silicon dioxide. In order to realize the shell structure on the surface of the inner core, the embodiment of the present application adopts a pickering emulsion method, that is, the phase change material is an oil phase, water is used as a dispersant, and nano-silicon dioxide is used as a stabilizer to stabilize the emulsion, so that under stirring, an emulsion of surface nano-silicon dioxide and internal phase change material can be formed. By adding a silane coupling agent to the emulsion, the silane coupling agent is first hydrolyzed and bonded with the nano-silicon dioxide. After bonding, the nano-silicon dioxide has a large number of double bond structures. When the temperature is increased, the initiator decomposes to generate free radicals, and the nano-silicon dioxide containing double bonds and the silane coupling agent undergo free radical polymerization to form a shell layer of the phase change material. Unreacted double bonds will remain in the shell material, and the unreacted double bonds will form chemical bonds of CC bonds with the three-dimensional cross-linked network. Combined with Figure 2 As shown, the bending curve is a three-dimensional cross-linked network, and the particles on the bending curve are phase change materials. The phase change material is fixed on the three-dimensional cross-linked network by chemical bonding, thereby avoiding its sedimentation in the solution.
[0055] In some exemplary embodiments, the mass ratio of the polymer to the silicon dioxide is 1:1 to 1:1000, which can form a shell layer on the surface of the phase change material to wrap the phase change material, and the shell layer and the three-dimensional cross-linked network are covalently cross-linked by chemical bonding to achieve the position fixation of the phase change material on the three-dimensional cross-linked network, which can effectively solve the problem that the phase change material is easy to flow in the solid electrolyte, and is conducive to improving the cycle performance and safety performance of lithium metal batteries. In some exemplary embodiments, the mass ratio of the polymer to the silicon dioxide is 1:1 to 1:100.
[0056] In some exemplary embodiments, the silane coupling agent contains an oxygen-containing group, the oxygen-containing group is used for hydrolysis, and the oxygen-containing group includes any one of an alkoxy group, a siloxy group, or a group shown in formula a;
[0057]
[0058] Among them, the * end is the free end.
[0059] In some exemplary embodiments, the silane coupling agent is selected from any one of the substances shown in Formula I;
[0060]
[0061] R1 is selected from any one of C1-C5 siloxy, C1-C5 alkoxy or the group represented by formula a;
[0062] R2 is selected from any one of the groups shown in formula b or the groups shown in formula c;
[0063]
[0064]
[0065] R3 and R5 are independently selected from any one of C1-C3 alkylene, R4 is selected from any one of H and C1-C3 alkyl, and n is 0 or 1.
[0066] In some exemplary embodiments, the silane coupling agent includes one or more of methacryloxypropyltrimethoxysilane, vinyltri(2-methoxyethoxy)silane, allyltrimethoxysilane, allyltri(trimethylsiloxy)silane, and (2-methylallyl)trimethylsilane.
[0067] In some exemplary embodiments, the phase change temperature of the phase change material is 30-85°C; exemplarily, the phase change temperature of the phase change material is a range consisting of any two values of 30°C, 40°C, 50°C, 60°C, 70°C, 80°C, and 85°C. Preferably, the phase change temperature of the phase change material is 65°C-75°C; exemplarily, the phase change temperature of the phase change material is a range consisting of any two values of 65°C, 68°C, 70°C, 73°C, and 75°C. In the embodiment of the present application, by introducing a phase change material into the gel electrolyte, the phase change material itself can absorb the heat generated by the lithium metal battery during the cycle during the phase change process, thereby avoiding heat accumulation inside the lithium metal battery and suppressing the temperature rise and thermal runaway of the lithium metal battery during the cycle.
[0068] In some exemplary embodiments, the phase change material includes C 20 To C 50At least one of a higher aliphatic hydrocarbon, a higher fatty acid, a higher fatty acid ester or a higher fatty alcohol. For example, the general formula of the higher aliphatic hydrocarbon is C n H 2n+2 , n is in the range of 20 to 50; for example, the higher aliphatic hydrocarbon may be: C 20 H 42 , C 25 H 52 , C 30 H 62 , C 40 H 82 , C 50 H 102 For example, the general formula of the higher fatty acid is C n H 2n+1 COOH, n is in the range of 10 to 50; for example, the higher fatty acid may be: C 10 H 21 COOH, C 20 H 41 COOH, C 25 H 51 COOH, C 30 H 61 COOH, C 40 H 81 COOH, C 50 H 101 The general formula of the higher fatty acid ester is C n H 2n+1 COOR, R is generally an alkyl group or other non-H group, and n is in the range of 20 to 50; for example, the higher fatty acid ester can be: C 20 H 41 COOCH3, C 25 H 51 COOCH2CH3、C 30 H 61 COOCH3, C 40 H 81 COOCH3, C 50 H 101 COOCH2CH3. The general formula of the higher fatty alcohol is C n H 2n+1 OH, n is in the range of 20 to 50; for example, the higher fatty alcohol may be: C 20 H 41 OH, C 25 H 51 OH, C 30 H 61 OH, C 40 H 81 OH, C 50 H 101OH.
[0069] In some exemplary embodiments, the average particle size of the phase change material is 0.1 μm to 1 μm; exemplarily, the average particle size of the phase change material is in the range of any two values of 0.1 μm, 0.2 μm, 0.4 μm, 0.6 μm, 0.8 μm, and 1.0 μm. Since the phase change material does not conduct ions, an average particle size of the phase change material that is too large will hinder ion transport and cause uneven lithium deposition, and an average particle size that is too small will not be conducive to preparation. Therefore, the embodiment of the present application uses a phase change material with an average particle size of 0.1 μm to 1 μm.
[0070] In some exemplary embodiments, the thickness of the shell layer is 1nm to 10nm; exemplarily, the thickness of the shell layer is in the range of any two values of 1nm, 2nm, 4nm, 6nm, 8nm, and 10nm. When the thickness of the shell layer is too thin, it will affect the covalent crosslinking between the phase change material and the three-dimensional crosslinked network, and affect the position fixation of the phase change material on the three-dimensional crosslinked network. When the thickness of the shell layer is too thick, it will affect the heat absorption effect of the phase change material. The thickness of the shell layer is related to the amount of the silane coupling agent added. Specifically, the more the amount of the silane coupling agent added, the thicker the thickness of the shell layer.
[0071] In some exemplary embodiments, the three-dimensional cross-linked network is obtained by polymerization of monomers; the monomers include at least one of polyoxyethylene and its derivatives, polyvinylidene fluoride and its derivatives, or polycarbonate and its derivatives; preferably, the polyoxyethylene derivative includes at least one of branched polyoxyethylene, polyoxyethylene / polycarbonate block copolymer, and polyoxyethylene / polysulfone block copolymer; the polyvinylidene fluoride derivative includes at least one of vinylidene fluoride / trifluoroethylene copolymer and vinylidene fluoride / hexafluoropropylene copolymer; the polycarbonate derivative includes at least one of branched polycarbonate and polycarbonate / polyoxyethylene copolymer.
[0072] In some exemplary embodiments, the cross-linking agent is a compound containing multiple unsaturated double bonds in the molecule, including one or more of divinylbenzene, diisocyanate, and N,N-methylenebisacrylamide.
[0073] The monomer and the cross-linking agent are polymerized by thermal initiation or ultraviolet initiation to obtain a three-dimensional cross-linked network. For example, the monomer is a long-chain polyoxyethylene and its derivatives modified by terminal double bonds, a long-chain polyvinylidene fluoride and its derivatives modified by terminal double bonds, or a long-chain polycarbonate and its derivatives modified by terminal double bonds and a cross-linking agent are polymerized by thermal initiation or ultraviolet initiation; the above monomers and shell materials can all be used as cross-linking agents.
[0074] In some exemplary embodiments, the initiator includes one or more of benzoyl peroxide, potassium persulfate, ammonium persulfate, azobisisobutyronitrile or azobisisoheptanenitrile.
[0075] The specific mechanism of the formation of a three-dimensional cross-linked network is as follows: the polymerizable double bonds (i.e., double bonds) induce a chain growth reaction after the initiator decomposes to produce free radicals, so the system needs to have three basic raw materials: an initiator, a cross-linking agent, and a polymerizable monomer (i.e., a monomer); in the embodiment of the present application, polyoxyethylene modified with terminal double bonds is selected as both a polymerizable monomer and a cross-linking agent, and thermal initiation or ultraviolet initiation is selected according to the type of initiator to promote the decomposition of the initiator. If the above conditions are met, a three-dimensional cross-linked network can be formed.
[0076] In some exemplary embodiments, the mass percentage of the phase change material in the gel electrolyte is 1% to 10%; illustratively, the mass percentage of the phase change material in the gel electrolyte is in a range consisting of any two values of 1%, 3%, 5%, 7%, 9%, and 10%. Preferably, the mass percentage of the phase change material in the gel electrolyte is 4% to 6%; illustratively, the mass percentage of the phase change material in the gel electrolyte is in a range consisting of any two values of 4%, 5%, and 6%.
[0077] The electrolyte is a common commercial lithium ion electrolyte, including an organic solvent and a lithium salt; the organic solvent includes a carbonate solvent, an ether solvent, a sulfone solvent, other aprotic solvents or a combination thereof; wherein the carbonate solvent includes diethyl carbonate (DEC), dimethyl carbonate (DMC), dipropyl carbonate (DPC), methyl propyl carbonate (MPC), ethyl propyl carbonate (EPC), ethyl methyl carbonate (MEC), ethylene carbonate (EC), propylene carbonate (PC), butylene carbonate Ester (BC), vinyl ethylene carbonate (VEC), fluoroethylene carbonate (FEC), 1,2-difluoroethylene carbonate, 1,1-difluoroethylene carbonate, 1,1,2-trifluoroethylene carbonate, 1,1,2,2-tetrafluoroethylene carbonate, 1-fluoro-2-methylethylene carbonate, 1-fluoro-1-methylethylene carbonate, 1,2-difluoro-1-methylethylene carbonate, 1,1,2-trifluoro-2-methylethylene carbonate or trifluoromethylethylene carbonate. A combination of one or more of the following: The ether solvent includes tetrahydrofuran, 2-methyltetrahydrofuran, 1,3-dioxolane, 2-methyl1,3-dioxolane, 4-methyl1,3-dioxolane, 1,3-dioxane, 1,4-dioxane, dimethoxypropane, dimethoxymethane, 1,1-dimethoxyethane, 1,2-dimethoxyethane, diethoxymethane, 1,1-diethoxyethane, 1,2-diethoxyethane, ethoxymethoxymethane, 1,1-ethoxymethoxyethane or 1,2-ethoxymethoxyethane. The sulfone solvent includes cyclopentane, dimethyl sulfoxide, methylcyclopentane, etc. Other organic solvents include 1,3-dimethyl-2-imidazolidinone, formamide, dimethylformamide, acetonitrile, trimethyl phosphate, triethyl phosphate, trioctyl phosphate or phosphate. Lithium salts include lithium hexafluorophosphate (LiPF6), lithium bis(oxalatoborate) (LiB(C2O4)2, LiBOB), lithium difluorooxalatoborate (LiBF2(C2O4, LiDFOB), lithium tetrafluoroborate (LiBF4), lithium hexafluoroantimonate (LiSbF6), lithium hexafluoroarsenate (LiAsF6), lithium perfluorobutylsulfonate (LiC4F9SO3), lithium perchlorate (LiClO4), lithium aluminate (LiAlO2), lithium tetrachloroaluminate (LiAlCl4), lithium bis(sulfonyl imide) (LiN(C x F 2x+1 SO2)(C y F 2y+1 SO2), wherein x and y are natural numbers), a combination of one or more of lithium bis(fluorosulfonyl)imide (LiFSI), lithium bis(trifluoromethanesulfonyl)imide (LiTFSI), lithium chloride (LiCl) or lithium fluoride (LiF).
[0078] The electrolyte may further include an electrolyte additive, and the electrolyte additive may be, but is not limited to, one or more of fluoroethylene carbonate (FEC) and fluorodimethyl carbonate (FDMC).
[0079] The second aspect of the present application provides a method for preparing any one of the above-mentioned lithium metal batteries, wherein the preparation of the gel electrolyte comprises the following steps:
[0080] (1) adding a silane coupling agent to a material containing a phase change material and silicon dioxide to obtain an emulsion;
[0081] Specifically, the phase change material is first mixed with water and heated, then nano silicon dioxide is added to the mixed solution and stirred evenly, and then a silane coupling agent is added and mixed evenly to obtain a stable pickering emulsion.
[0082] The pickering emulsion method is adopted, the phase change material is the oil phase, water is used as a dispersant, and nano-silica is used as a stabilizer for stabilizing the emulsion; when the silane coupling agent is added, the oxygen-containing groups on the silane coupling agent are first hydrolyzed, and then bonded to the solid nano-silica surface after hydrolysis to obtain nano-silica containing double bonds.
[0083] (2) adding an initiator to the emulsion obtained in (1) under an inert atmosphere, and stirring at 60° C. to 80° C. to obtain a phase change material having a core-shell structure;
[0084] Specifically, in an argon atmosphere, an initiator is added to the emulsion obtained in (1), and the mixture is stirred at 60° C. to 80° C. for 10 to 12 hours to obtain a phase change material having a core-shell structure.
[0085] The double bonds on the nano-silica are decomposed at high temperature under the action of the initiator to generate free radicals, which then undergo free radical polymerization with the silane coupling agent to obtain a phase change material with a core-shell structure.
[0086] (3) uniformly mixing the phase change material obtained in (2), the electrolyte, the polymerizable monomer, the crosslinking agent and the initiator, and reacting them at 65° C. to 75° C. to obtain the gel electrolyte;
[0087] Specifically, in a dry argon atmosphere, the phase change material obtained in (2), the electrolyte, the polymerizable monomer, the crosslinking agent and the initiator are mixed uniformly, injected into a lithium metal battery and reacted at 65° C. to 75° C. for 12 to 14 hours.
[0088] After adding the phase change material powder during the preparation process, it needs to be fully stirred to achieve uniform dispersion of the phase change material in the gel electrolyte precursor, that is, the phase change material is dispersed into a colloidal solution to ensure that the phase change material does not agglomerate in the preparation of the gel electrolyte precursor, which is beneficial for the gel electrolyte to have the function of endothermic phase change; the dispersed precursor is polymerized by heat initiation, and finally the phase change material and the three-dimensional cross-linked network are fixed in position through CC bonding, avoiding the unfavorable phenomena such as uneven distribution and aggregation of the phase change material in the gel electrolyte due to sedimentation; and the problem that the phase change material is easy to flow during the phase change process is solved, thereby improving the cycle performance and safety performance of lithium metal batteries.
[0089] The third aspect of the present application provides an electrical device, wherein the electrical device comprises the above-mentioned lithium metal battery. The electrical device of the present application includes, but is not limited to, a laptop computer, an electronic book player, a portable phone, a portable fax machine, a portable copier, a portable printer, a head-mounted stereo headset, a video recorder, an LCD TV, a portable cleaner, a portable CD player, a mini-disc, a transceiver, an electronic notepad, a calculator, a memory card, a portable recorder, a radio, a backup power supply, a motor, a car, a motorcycle, a power-assisted bicycle, a bicycle, a lighting fixture, a toy, a game console, a clock, an electric tool, a flashlight, a camera, a large household battery, and a lithium-ion capacitor, etc.
[0090] Example
[0091] The following examples more specifically describe the disclosure of the present application, which are intended for illustrative purposes only, as it will be apparent to those skilled in the art that various modifications and variations may be made within the scope of the disclosure of the present application. Unless otherwise stated, all parts, percentages, and ratios reported in the following examples are by weight, and all reagents used in the examples are commercially available or synthesized according to conventional methods and can be used directly without further processing, and the instruments used in the examples are commercially available.
[0092] Example 1
[0093] Preparation of negative electrode
[0094] Cut the 30um thick lithium copper composite tape into specifications of (40mm 60mm) for later use.
[0095] Preparation of positive electrode
[0096] The positive electrode ternary active material NMC811, conductive carbon black (Super P), and polyvinylidene fluoride (PVDF) are mixed in a weight ratio of 96:2:2, and N-methylpyrrolidone (NMP) is added as a solvent to prepare a slurry with a solid content of 0.75. The slurry is stirred evenly, and the slurry is evenly coated on both sides of the positive electrode collector aluminum foil, and dried at 90°C to obtain a positive electrode sheet. After coating, the sheet is cut into specifications of (38mm58mm) for standby use.
[0097] Preparation of phase change materials
[0098] Paraffin wax (i.e., phase change material) with phase change function is mixed with water at a mass ratio of 1:50 and heated to 80°C, then 1wt% of nano-silicon dioxide is added to the mixed solution in sequence and stirred evenly, and then 0.1wt% of methacryloxypropyltrimethoxysilane (i.e., silane coupling agent) is added and mixed evenly to obtain a stable pickering emulsion; in an argon atmosphere, 50mg / L of ammonium persulfate (i.e., initiator) is added to the emulsion, stirred at 65°C for 12h, and a solution containing a paraffin core-shell structure is obtained; the solution is centrifuged and dried to obtain a paraffin core-shell powder with a paraffin core-shell structure having a phase change function.
[0099] The average particle size of the paraffin core-shell powder is 0.3 μm, and the shell thickness of the paraffin core-shell powder is 2.5 nm.
[0100] Preparation of gel electrolyte
[0101] In a dry argon atmosphere, ethylene carbonate (EC) and 1,1,2,2-tetrafluoro-3-(1,1,2,2-tetrafluoroethoxy)propane (TTE) are mixed in a mass ratio of EC:TTE=2:3, and then paraffin core-shell powder (paraffin), polyoxyethylene (PEO) modified with a double bond at the end (i.e., a monomer of a three-dimensional cross-linked network), azobisisobutyronitrile (i.e., an initiator), fluoroethylene carbonate (FEC), fluorodimethyl carbonate (FDMC) and lithium salt lithium hexafluorophosphate (LiPF6) are added to the mixed solvent and dissolved and mixed evenly to obtain a polymerizable phase change electrolyte with a lithium salt concentration of 1.0M; i.e., 1.0M LiPF6 in20%FEC+30%FDMC+20%EC+26%TTE+2%paraffin+2%PEO.
[0102] It should be noted that in the preparation of the gel electrolyte, the terminal double-bond-modified polyethylene oxide (PEO) and the shell material in the phase change material can be used as a cross-linking agent, so there is no need to add other types of cross-linking agents.
[0103] In the following embodiments, the same substances have the same functions and are not described in detail.
[0104] Preparation of lithium metal batteries
[0105] Polyethylene (PE) with a thickness of 15μm is selected as the isolation membrane, and a Z-shaped stacking method is adopted. The positive electrode sheet and the negative electrode sheet are on both sides of the separator, and the isolation membrane is between the electrode sheets. After stacking, the pole ears are welded and then placed in an aluminum-plastic film. After top and side sealing, liquid injection, packaging, and heating and curing, a lithium metal stacked battery is finally obtained.
[0106] Example 2
[0107] Different from Example 1, the preparation of the gel electrolyte is as follows:
[0108] Preparation of gel electrolyte
[0109] In a dry argon atmosphere, ethylene carbonate (EC) and 1,1,2,2-tetrafluoro-3-(1,1,2,2-tetrafluoroethoxy)propane (TTE) are mixed in a mass ratio of EC:TTE=2:3, and then paraffin core-shell powder (paraffin), terminal double-bond modified polyethylene oxide (PEO), azobisisobutyronitrile, fluoroethylene carbonate (FEC), fluorodimethyl carbonate (FDMC) and lithium salt lithium hexafluorophosphate (LiPF6) are added to the mixed solvent and dissolved and mixed evenly to obtain a polymerizable phase change electrolyte with a lithium salt concentration of 1.0M; that is, 1.0M LiPF6 in20%FEC+30%FDMC+20%EC+24%TTE+4%paraffin+2%PEO.
[0110] Example 3
[0111] Different from Example 1, the preparation of the gel electrolyte is as follows:
[0112] Preparation of gel electrolyte
[0113] In a dry argon atmosphere, ethylene carbonate (EC) and 1,1,2,2-tetrafluoro-3-(1,1,2,2-tetrafluoroethoxy)propane (TTE) are mixed in a mass ratio of EC:TTE=2:3, and then paraffin core-shell powder (paraffin), terminal double-bond modified polyethylene oxide (PEO), azobisisobutyronitrile, fluoroethylene carbonate (FEC), fluorodimethyl carbonate (FDMC) and lithium salt lithium hexafluorophosphate (LiPF6) are added to the mixed solvent and dissolved and mixed evenly to obtain a polymerizable phase change electrolyte with a lithium salt concentration of 1.0M; that is, 1.0M LiPF6 in20%FEC+30%FDMC+20%EC+22%TTE+6%paraffin+2%PEO.
[0114] Example 4
[0115] Different from Example 1, regarding the preparation of the phase change material, the phase change material of Example 4 is hexatriacontane with phase change function, that is, a hexatriacontane core-shell powder with a hexatriacontane core-shell structure with phase change function is obtained.
[0116] And, preparation of gel electrolyte
[0117] In a dry argon atmosphere, ethylene carbonate (EC) and 1,1,2,2-tetrafluoro-3-(1,1,2,2-tetrafluoroethoxy)propane (TTE) are mixed in a mass ratio of EC:TTE=2:3, and then hexatriacontane core-shell powder (Hexatriacontane), terminal double-bond modified polyethylene oxide (PEO), azobisisobutyronitrile, fluoroethylene carbonate (FEC), fluorodimethyl carbonate (FDMC) and lithium salt lithium hexafluorophosphate (LiPF6) are added to the mixed solvent and dissolved and mixed evenly to obtain a polymerizable phase change electrolyte with a lithium salt concentration of 1.0M; that is, 1.0M LiPF6 in 20%FEC+30%FDMC+20%EC+26%TTE+2%Hexatriacontane+2%PEO.
[0118] The average particle size of the hexatriacontane core-shell powder is 0.3 μm, and the shell thickness of the hexatriacontane core-shell powder is 2.5 nm.
[0119] Example 5
[0120] Different from Example 4, the preparation of the gel electrolyte is as follows:
[0121] In a dry argon atmosphere, ethylene carbonate (EC) and 1,1,2,2-tetrafluoro-3-(1,1,2,2-tetrafluoroethoxy)propane (TTE) are mixed in a mass ratio of EC:TTE=2:3, and then hexatriacontane core-shell powder (Hexatriacontane), terminal double-bond modified polyethylene oxide (PEO), azobisisobutyronitrile, fluoroethylene carbonate (FEC), fluorodimethyl carbonate (FDMC) and lithium salt lithium hexafluorophosphate (LiPF6) are added to the mixed solvent and dissolved and mixed evenly to obtain a polymerizable phase change electrolyte with a lithium salt concentration of 1.0M; that is, 1.0M LiPF6 in 20%FEC+30%FDMC+20%EC+24%TTE+4%Hexatriacontane+2%PEO.
[0122] Example 6
[0123] Different from Example 4, the preparation of the gel electrolyte is as follows:
[0124] In a dry argon atmosphere, ethylene carbonate (EC) and 1,1,2,2-tetrafluoro-3-(1,1,2,2-tetrafluoroethoxy)propane (TTE) are mixed in a mass ratio of EC:TTE=2:3, and then hexatriacontane core-shell powder (Hexatriacontane), terminal double-bond modified polyethylene oxide (PEO), azobisisobutyronitrile, fluoroethylene carbonate (FEC), fluorodimethyl carbonate (FDMC) and lithium salt lithium hexafluorophosphate (LiPF6) are added to the mixed solvent and dissolved and mixed evenly to obtain a polymerizable phase change electrolyte with a lithium salt concentration of 1.0M; that is, 1.0M LiPF6 in 20%FEC+30%FDMC+20%EC+22%TTE+6%Hexatriacontane+2%PEO.
[0125] Example 7
[0126] Different from Example 1, regarding the preparation of the phase change material, the phase change material of Example 7 is lauric acid with phase change function, that is, a lauric acid core-shell powder with a lauric acid core-shell structure with phase change function is obtained.
[0127] And, preparation of gel electrolyte
[0128] In a dry argon atmosphere, ethylene carbonate (EC) and 1,1,2,2-tetrafluoro-3-(1,1,2,2-tetrafluoroethoxy)propane (TTE) are mixed in a mass ratio of EC:TTE=2:3, and then lauric acid core-shell powder (lauricacid), terminal double-bond modified polyethylene oxide (PEO), azobisisobutyronitrile, fluoroethylene carbonate (FEC), fluorodimethyl carbonate (FDMC) and lithium salt lithium hexafluorophosphate (LiPF6) are added to the mixed solvent and dissolved and mixed evenly to obtain a polymerizable phase change electrolyte with a lithium salt concentration of 1.0M; that is, 1.0M LiPF6 in20%FEC+30%FDMC20%EC+26%TTE+2%lauric acid+2%PEO.
[0129] The average particle size of the lauric acid core-shell powder is 0.3 μm, and the shell thickness of the lauric acid core-shell powder is 2.5 nm.
[0130] Example 8
[0131] Different from Example 7, the preparation of the gel electrolyte is as follows:
[0132] In a dry argon atmosphere, ethylene carbonate (EC) and 1,1,2,2-tetrafluoro-3-(1,1,2,2-tetrafluoroethoxy)propane (TTE) are mixed in a mass ratio of EC:TTE=2:3, and then lauric acid core-shell powder (lauricacid), terminal double-bond modified polyethylene oxide (PEO), azobisisobutyronitrile, fluoroethylene carbonate (FEC), fluorodimethyl carbonate (FDMC) and lithium salt lithium hexafluorophosphate (LiPF6) are added to the mixed solvent and dissolved and mixed evenly to obtain a polymerizable phase change electrolyte with a lithium salt concentration of 1.0M; that is, 1.0M LiPF6 in20%FEC+30%FDMC+20%EC+24%TTE+4%lauric acid+2%PEO.
[0133] Example 9
[0134] Different from Example 7, the preparation of the gel electrolyte is as follows:
[0135] In a dry argon atmosphere, ethylene carbonate (EC) and 1,1,2,2-tetrafluoro-3-(1,1,2,2-tetrafluoroethoxy)propane (TTE) are mixed in a mass ratio of EC:TTE=2:3, and then lauric acid core-shell powder (lauricacid), terminal double-bond modified polyethylene oxide (PEO), azobisisobutyronitrile, fluoroethylene carbonate (FEC), fluorodimethyl carbonate (FDMC) and lithium salt lithium hexafluorophosphate (LiPF6) are added to the mixed solvent and dissolved and mixed evenly to obtain a polymerizable phase change electrolyte with a lithium salt concentration of 1.0M; that is, 1.0M LiPF6 in20%FEC+30%FDMC+20%EC+22%TTE+6%lauric acid+2%PEO.
[0136] Example 10
[0137] Different from Example 4, the preparation of the gel electrolyte is as follows:
[0138] In a dry argon atmosphere, ethylene carbonate (EC) and 1,1,2,2-tetrafluoro-3-(1,1,2,2-tetrafluoroethoxy)propane (TTE) are mixed in a mass ratio of EC:TTE=2:3, and then hexatriacontane core-shell powder (Hexatriacontane), terminal double-bond modified polyethylene oxide (PEO), azobisisobutyronitrile, fluoroethylene carbonate (FEC), fluorodimethyl carbonate (FDMC) and lithium salt lithium hexafluorophosphate (LiPF6) are added to the mixed solvent and dissolved and mixed evenly to obtain a polymerizable phase change electrolyte with a lithium salt concentration of 1.0M; that is, 1.0M LiPF6 in 20%FEC+30%FDMC+20%EC+27%TTE+1%Hexatriacontane+2%PEO.
[0139] Embodiment 11
[0140] Different from Example 4, the preparation of the gel electrolyte is as follows:
[0141] In a dry argon atmosphere, ethylene carbonate (EC) and 1,1,2,2-tetrafluoro-3-(1,1,2,2-tetrafluoroethoxy)propane (TTE) are mixed in a mass ratio of EC:TTE=2:3, and then hexatriacontane core-shell powder (Hexatriacontane), terminal double-bond modified polyethylene oxide (PEO), azobisisobutyronitrile, fluoroethylene carbonate (FEC), fluorodimethyl carbonate (FDMC) and lithium salt lithium hexafluorophosphate (LiPF6) are added to the mixed solvent and dissolved and mixed evenly to obtain a polymerizable phase change electrolyte with a lithium salt concentration of 1.0M; that is, 1.0M LiPF6 in 20%FEC+30%FDMC+20%EC+18%TTE+10%Hexatriacontane+2%PEO.
[0142] Example 12
[0143] Different from Example 4, the preparation of the gel electrolyte is as follows:
[0144] In a dry argon atmosphere, ethylene carbonate (EC) and 1,1,2,2-tetrafluoro-3-(1,1,2,2-tetrafluoroethoxy)propane (TTE) are mixed in a mass ratio of EC:TTE=2:3, and then hexatriacontane core-shell powder (Hexatriacontane), terminal double-bond modified polyethylene oxide (PEO), azobisisobutyronitrile, fluoroethylene carbonate (FEC), fluorodimethyl carbonate (FDMC) and lithium salt lithium hexafluorophosphate (LiPF6) are added to the mixed solvent and dissolved and mixed evenly to obtain a polymerizable phase change electrolyte with a lithium salt concentration of 1.0M; that is, 1.0M LiPF6 in 20%FEC+30%FDMC+20%EC+27.5%TTE+0.5%Hexatriaconta ne+2%PEO.
[0145] Embodiment 13
[0146] Different from Example 4, the preparation of the gel electrolyte is as follows:
[0147] In a dry argon atmosphere, ethylene carbonate (EC) and 1,1,2,2-tetrafluoro-3-(1,1,2,2-tetrafluoroethoxy)propane (TTE) are mixed in a mass ratio of EC:TTE=2:3, and then hexatriacontane core-shell powder (Hexatriacontane), terminal double-bond modified polyethylene oxide (PEO), azobisisobutyronitrile, fluoroethylene carbonate (FEC), fluorodimethyl carbonate (FDMC) and lithium salt lithium hexafluorophosphate (LiPF6) are added to the mixed solvent and dissolved and mixed evenly to obtain a polymerizable phase change electrolyte with a lithium salt concentration of 1.0M; that is, 1.0M LiPF6 in 20%FEC+30%FDMC+20%EC+13%TTE+15%Hexatriacontane+2%PEO.
[0148] Embodiment 14
[0149] Involving the preparation of two phase change materials, the preparation of paraffin core-shell powder is the same as in Example 1;
[0150] The difference from Example 1 is that it also includes: preparation of lauric acid core-shell powder;
[0151] Preparation of lauric acid core-shell powder
[0152] The lauric acid with phase change function and water are mixed at a mass ratio of 1:50 and heated, and then nano-silicon dioxide is added to the mixed solution in sequence and stirred evenly, and then methacryloxypropyltrimethoxysilane is added and mixed evenly to obtain a stable pickering emulsion; in an argon atmosphere, ammonium persulfate is added to the emulsion, and stirred at 65°C for 12 hours to obtain a solution containing a lauric acid core-shell structure; the solution is centrifuged and dried to obtain a lauric acid core-shell powder with a lauric acid core-shell structure having a phase change function.
[0153] And, preparation of gel electrolyte
[0154] In a dry argon atmosphere, an organic solvent of ethylene carbonate (EC) and 1,1,2,2-tetrafluoro-3-(1,1,2,2-tetrafluoroethoxy)propane (TTE) are mixed in a mass ratio of EC:TTE=2:3, and then paraffin core-shell powder (paraffin), lauric acid core-shell powder (lauric acid), polyoxyethylene modified with a double bond at the end (PEO), azobisisobutyronitrile, fluoroethylene carbonate (FEC), fluorodimethyl carbonate (FDMC) and lithium salt lithium hexafluorophosphate (LiPF6) are added to the organic solvent and dissolved and mixed evenly to obtain a polymerizable phase change electrolyte with a lithium salt concentration of 1.0M; that is, 1M LiPF6 in 20%FEC+30%FDMC+20%EC+24%TTE+2%paraffin+2%lauric acid+2%PEO.
[0155] Comparative Example 1
[0156] Different from Example 1, no phase change material is added in the preparation of the gel electrolyte.
[0157] Comparative Examples 2 to 4
[0158] Different from Example 1, a phase change material with phase change function is directly put into the preparation of the gel electrolyte to replace the phase change material with a core-shell structure. The phase change material in Comparative Example 2 is paraffin, the phase change material in Comparative Example 3 is hexatriacontane, and the phase change material in Comparative Example 4 is lauric acid. The mass percentage of the above phase change materials in the 1.0M LiPF6 polymerizable phase change electrolyte is 4%.
[0159] Critical failure temperature test:
[0160] The lithium metal battery is placed vertically in a test box. The temperature inside the test box is raised to 200±2℃ at a rate of 5±2℃ per minute and maintained for 15 minutes. During the test, the temperature of the lithium metal battery and the box temperature are monitored in real time. When the temperature rise of the lithium metal battery exceeds 10℃ / s, the temperature of the lithium metal battery at this time is recorded, which is the critical failure temperature of the lithium metal battery.
[0161] Cycle performance test:
[0162] At 25°C, charge the lithium metal battery to 4.3V at a constant current of 0.3C, and then charge it at a constant voltage to a current of 0.025C. At this time, the lithium metal battery is fully charged. Record the charging capacity at this time, which is the first cycle charging capacity. After the lithium metal battery is allowed to stand for 5 minutes, discharge it to 2.8V at a constant current of 0.5C and let it stand for 5 minutes. This is a cyclic charge and discharge process. Record the discharge capacity at this time, which is the first cycle discharge capacity. Repeat the above charge and discharge cycle process until the current cycle discharge capacity decays to 80% of the first cycle discharge capacity or the lithium metal battery fails. Among them, capacity retention rate = discharge capacity of the current cycle / first cycle discharge capacity.
[0163] It should be noted that, since Comparative Example 2 was the first to decay and fail, the capacity retention rate of 88% at the time of failure was taken as the reference capacity retention rate of all tested lithium metal batteries. The cycle numbers of lithium metal batteries in different groups were compared, and the performance data of all lithium metal batteries are shown in Table 1.
[0164] Table 1
[0165]
[0166]
[0167] It can be seen from the data in Table 1 that in the preparation process of the gel electrolyte, no phase change material or phase change substance is added to Comparative Example 1. Although the number of cycles corresponding to 88% of the capacity retention rate can reach 200cls, its critical failure temperature is only 130.2°C, which is about 14°C lower than the critical failure temperature of Example 1 of 144.2°C, and the number of cycles of Example 1 at 88% of the capacity retention rate can also reach 195cls; the surface of the phase change material in Comparative Examples 2 to 4 is not coated with a shell structure, that is, the phase change material is only a phase change material without a shell structure. Combined with the data in Table 1, Although the critical failure temperatures of Examples 2 to 4 are slightly higher than that of Comparative Example 1, this is because phase change materials are introduced into the gel electrolyte. The introduction of phase change materials can utilize their own phase change endothermic characteristics to delay the temperature rise of the battery system, thereby increasing the critical failure temperature of the lithium metal battery; however, since the unfixed phase change material is easy to flow during the phase change process, and then generate gaps in the gel electrolyte, it will affect the ion conduction inside the gel electrolyte, resulting in a lower number of cycles for Comparative Examples 2 to 4 at a capacity retention rate of 88% (all not exceeding 130cls, and the lowest is only 82cls).
[0168] The phase change material in Examples 1 to 3 is a paraffin core-shell structure powder, the phase change material is paraffin with a phase change function, and its phase change temperature is 62°C; the phase change material in Examples 4 to 5 is a hexatriacontane core-shell structure powder, the phase change material is hexatriacontane with a phase change function, and its phase change temperature is 73°C; the phase change material in Examples 7 to 9 is a lauric acid core-shell structure powder, the phase change material is lauric acid with a phase change function, and its phase change temperature is 43°C; It can be seen from the data in Table 1 that the critical failure temperature of Examples 1 to 3 is 144.2 to 161.8°C, which corresponds to a cycle number of about 190cls at a capacity retention rate of 88%, which is much higher than the cycle number of 112cls (about 78cls higher) at a capacity retention rate of 88% in Comparative Example 2 (the same phase change material, but without a shell structure); the critical failure temperature of Examples 4 to 6 is 148.4 to 169.2°C , the minimum number of cycles corresponding to a capacity retention rate of 88% is 188cls, and the maximum number of cycles can reach 197cls, which is much higher than the 125cls (about 63-72cls higher) of the comparative example 3 (the same phase change material, but without a shell structure) at a capacity retention rate of 88%; the critical failure temperatures of embodiments 7-9 are 139.2-156.4°C, and the number of cycles corresponding to a capacity retention rate of 88% is higher than 180cls, which is much higher than the 82 (about 100-110cls higher) of the comparative example 4 (the same phase change material, but without a shell structure) at a capacity retention rate of 88%; it can be seen that the phase change material is fixed on the three-dimensional cross-linked network in the gel electrolyte by chemical bonding, which can effectively prevent the phase change material from flowing due to the phase change process, thereby avoiding local accumulation and voids in the phase change material, so as to improve the cycle performance and safety of the lithium metal battery.
[0169] Moreover, by comparing Examples 1 to 3, Examples 4 to 6, and Examples 7 to 9, it can be seen that when tri-hexatriacontane with a phase change temperature of 73°C is applied to a lithium metal battery compared to paraffin with a phase change temperature of 62°C and lauric acid with a phase change temperature of 43°C, the lithium metal battery has a higher critical failure temperature and a greater number of cycles corresponding to a capacity retention rate of 88%. It can be seen that the phase change material with a phase change temperature of 65°C to 75°C is beneficial to absorbing heat energy during the cycle of the lithium metal battery and is beneficial to improving the cycle performance of the lithium metal battery.
[0170] In addition, by comparing Examples 4 to 6, 10 to 11 and Comparative Examples 5 to 6, it can be seen that the improvement of the critical failure temperature of the battery by the gel electrolyte is related to the amount of phase change material added. As the content of the phase change material increases, more phase change material can store more heat energy, thereby being able to suppress more serious thermal failure phenomena inside the battery, thereby increasing the critical failure temperature of the battery; however, since the phase change material does not have the property of conducting ions, too much phase change material will reduce the transmission path of lithium ions, thereby affecting the cycle performance of the lithium metal battery; and too low a content of phase change material has limited storage capacity for the heat energy generated inside the battery, and the improvement of the critical failure temperature is not obvious; it can be seen that the addition of a suitable amount of phase change material is conducive to improving the internal heat accumulation of the lithium metal battery and improving the cycle performance of the lithium metal battery, especially when the mass percentage of the phase change material in the gel electrolyte is 4% to 6%, the effect is optimal.
[0171] Example 14 is compared with Example 2 and Example 8 respectively. From the data in Table 1, it can be seen that the mixed use of multiple phase change materials can also improve the internal heat accumulation of lithium metal batteries and improve the cycle performance of lithium metal batteries.
[0172] The above description is only a preferred embodiment of the present application and is not intended to limit the present application. Any modifications, equivalent substitutions and improvements made within the spirit and principles of the present application should be included in the protection scope of the present application.
Claims
1. A lithium metal battery, characterized in that: Includes gel electrolyte; The gel electrolyte comprises a phase change material and a three-dimensional cross-linked network, the phase change material comprises an inner core and a shell layer on the surface of the inner core, and the inner core comprises a phase change substance; The phase change material is bonded to the three-dimensional cross-linked network; The three-dimensional cross-linked network is obtained by polymerization of monomers, wherein the monomers include at least one of polyoxyethylene and its derivatives, polyvinylidene fluoride and its derivatives, or polycarbonate and its derivatives.
2. The lithium metal battery according to claim 1, characterized in that The shell layer comprises a polymer and silicon dioxide, and the monomer of the polymer comprises a silane coupling agent containing a carbon-carbon double bond.
3. The lithium metal battery according to claim 2, characterized in that The mass ratio of the polymer to the silicon dioxide is 1:1 to 1:1000. Preferably, the mass ratio of the polymer to the silicon dioxide is 1:1 to 1:
100.
4. The lithium metal battery according to claim 2, characterized in that The silane coupling agent is selected from any one of the substances shown in formula I; R1 is selected from any one of C1-C5 siloxy, C1-C5 alkoxy or the group represented by formula a; R2 is selected from any one of the groups shown in formula b or the groups shown in formula c; R3 and R5 are independently selected from any one of C1-C3 alkylene, R4 is selected from any one of H and C1-C3 alkyl, and n is 0 or 1.
5. The lithium metal battery according to claim 2, characterized in that The silane coupling agent includes one or more of methacryloxypropyltrimethoxysilane, vinyltri(2-methoxyethoxy)silane, allyltrimethoxysilane, allyltri(trimethylsiloxy)silane, and (2-methylallyl)trimethylsilane.
6. The lithium metal battery according to claim 1, characterized in that The phase change temperature of the phase change material is 30 to 85°C; Preferably, the phase change temperature of the phase change material is 65°C to 75°C.
7. The lithium metal battery according to claim 1, characterized in that The phase change material includes C 20 To C 50 Higher aliphatic hydrocarbons, C 10 To C 50 Higher fatty acids, C 20 To C 50 Higher fatty acid esters or C 20 To C 50 At least one of higher fatty alcohols.
8. The lithium metal battery according to claim 1, characterized in that The average particle size of the phase change material is 0.1 μm to 1.0 μm.
9. The lithium metal battery according to claim 1, characterized in that The thickness of the shell layer is 1 nm to 10 nm.
10. The lithium metal battery according to claim 1, characterized in that The polyoxyethylene derivative comprises at least one of branched polyoxyethylene, polyoxyethylene / polycarbonate block copolymer, and polyoxyethylene / polysulfone block copolymer; The polyvinylidene fluoride derivative includes at least one of a vinylidene fluoride / trifluoroethylene copolymer and a vinylidene fluoride / hexafluoropropylene copolymer; The polycarbonate derivative includes at least one of branched polycarbonate and polycarbonate / polyethylene oxide copolymer.
11. The lithium metal battery according to claim 1, characterized in that The mass percentage of the phase change material in the gel electrolyte is 1% to 10%; Preferably, the mass percentage of the phase change material in the gel electrolyte is 4% to 6%.
12. The method for preparing a lithium metal battery according to any one of claims 1 to 11, characterized in that: The preparation method of the gel electrolyte comprises the following steps: (1) adding a silane coupling agent to a material containing a phase change material and silicon dioxide to obtain an emulsion; (2) adding an initiator to the emulsion obtained in (1) under an inert atmosphere, and stirring at 60° C. to 80° C. to obtain a phase change material having a core-shell structure; (3) The phase change material obtained in (2), the electrolyte, the polymerizable monomer, the crosslinking agent and the initiator are uniformly mixed and reacted at 65° C. to 75° C. to obtain the gel electrolyte.
13. An electrical device, characterized in that: The electrical device contains the lithium metal battery according to any one of claims 1 to 11.
Citation Information
Patent Citations
Gel polymer electrolyte with core-shell structure as well as preparation method and application thereof
CN110707357A
Three-dimensional network flame-retardant silica gel electrolyte, preparation method thereof and preparation method of gel lithium ion battery
CN111326790A